PENGARUH LINGKUNGAN KERJA FISIK DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Miftahul Nur Latifa; R. Taufiq Nur Muftiyanto; Indra Hastuti (JURNAL ILMIAH EDUNOMIKA, 2024)
This type of research is quantitative research. This research aims to determine the influence of the physical work environment and emotional intelligence on employee performance through job satisfaction as an intervening variable. Data collection in this study used a questionnaire given to 60 respondents at the Surakarta City Environmental Service. The analysis technique used is PLS (Partial Least Square) analysis through the Smart PLS 4.0 program. The results of this research show that the Physical Work Environment has a positive and significant effect on Job Satisfaction in the Surakarta City Environmental Service, Emotional Intelligence has a positive and significant effect on Job Satisfaction in the Surakarta City Environmental Service, the Physical Work Environment has a positive and significant effect on Employee Performance in the Department Surakarta City Environment, Emotional Intelligence has a positive and significant effect on Employee Performance in the Surakarta City Environmental Service, Job Satisfaction has a negative and significant effect on Employee Performance in the Surakarta City Environmental Service, Physical Work Environment has a negative and significant effect on Employee Performance through Job Satisfaction as an intervening variable in the Surakarta City Environmental Service, Emotional Intelligence has a negative and significant effect on Employee Performance through Job Satisfaction as an Intervening variable in the Surakarta City Environmental Service.